Referral to Treatment After Positive Screens for Unhealthy Drug Use in an Outpatient Veterans Administration Setting. Issue 3 (May 2020) - Hodgkin, Dominic; Gao, Wenwu; Larson, Mary Jo; Drebing, Charles E.; Merrick, Elizabeth L.; Pugatch, Marianne; Horgan, Constance M.; Zolotusky, Galina; Petry, Nancy M.; Saitz, Richard
Abstract : Objectives: To measure the rates and predictors of clinician recommendation for follow-up after a positive screen for unhealthy drug use, in a context of mandatory routine screening. To measure response to clinician recommendations and identification of new drug use diagnoses. Methods: Data are from a Veterans Health Administration (VHA) medical center that introduced mandatory routine screening for unhealthy drug use in outpatient primary care and mental health settings, using a validated single question. This study analyzed VHA electronic health records data for patients who screened positive for unhealthy drug use (n = 570) and estimated logistic regression models to identify the predictors of receiving a recommendation for any follow-up and for specialty substance use disorder (SUD) treatment. Bivariate tests were used for other analyses. Results: Among patients who screened positive for unhealthy drug use, 66% received no recommendation to return to primary care or another setting from the screening clinician. Further, among the 23% of patients who received a recommendation to visit specialty SUD treatment, only 25% completed the visit within 60 days. Six percent of all positive screens both received a referral to specialty SUD treatment and acted upon it. Conclusions: In the context of mandatory drug use screening using a single item, rates of clinician action and patient receipt of care appeared low. Improved follow-up will require health systems to provide more supports for clinicians and patients at each of the stages from positive screen to attending the follow-up appointment.